An Investment Agreement within the WTO for Sustainable Economic Development of Low-Income Countries - Anawaratna, Mahawella Adhikaramge Ajith (Curtin University, 2021)
The convergence of trade and investment within the WTO will contribute to the sustainable economic development of LICs and bring predictability to investment law. Therefore, this thesis proposes to establish a CIIA and an IIDSU to converge trade and investment. It further argues that the category of ‘developing countries’ in the WTO agreements is flawed. The thesis proposes a new category of LIC on the basis of their share of world trade and FDI.